Comparison of the Effects of Using Traditional Thai Musical Instruments and Carl Orff’s Instruments on Mentally Disabled Children’s Perception and Reaction to the Musical Elements - Tepika Rodsakan (Graduate School of Institut Seni Indonesia Yogyakarta, 2015)
This research dealt with the comparison of the effects of using traditional Thai musical instruments and Carl Orff’s instruments on mentally disabled children’s perception and reaction to the musical elements. The objectives of the research were 1) to study the results of the effects of using traditional Thai musical instruments on mentally disabled children’s perception and reaction to the musical elements 2) to study the results of the effects of Carl Orff’s instruments on mentally disabled children’s perception and reaction to the musical elements 3) to compare the results of the effects of using traditional Thai musical instruments and Carl Orff’s instruments on mentally disabled children’s perception and reaction to the musical elements. The sample used in the research were 11 educable mentally disabled children from Panyawutikorn School aged between 8-10 years old. The sample had been tested and confirmed by the psychologist to have IQ range from 50-70, to be non-sound sensitive and to be devoid of any multiple handicaps. The sample were selected using purposive sampling. The tool used in this research were an interactive 9-question test of the sample group’s perception and reaction to musical elements using traditional Thai musical instruments and Carl Orff’s instruments. The sample group responded accordingly to the different given tasks in the test including singing, physical movement, playing musical instruments and musically melodic creation. The data obtained are then analyzed using statistical calculation, i.e. median, percentage and mean. The test results revealed the following findings; the results were as follows: 1. Results of the effects of using traditional Thai musical instruments on mentally disabled children’s perception and reaction to the musical elements were found to be in the “good” criteria. 2. Results of the effects of using Carl Orff’s instruments on mentally disabled children’s perception and reaction to the musical elements were found to be in the “good” criteria. When considered each factor individually, the perception and reaction to sound was in the “fair” criteria while the perception and reaction to rhythm and melody were in the “good” criteria. 3. By comparing the results of the effect of using traditional Thai musical instruments and Carl Orff’s instruments on mentally disabled children’s perception and reaction to the musical elements, it was found to be different on the whole. When considered each factor individually, there was a difference in the perception of sound while there was no difference in perception and reaction to rhythm and melody.